Numerical Simulation of Hypoid Gear Hot Rolling Forming based on Anti-conjugate Principle Design Tool Pinion - Tang Hongyan; Deng Xiaozhong; Gao Zhenshan (Jixie chuandong)
Based on generating method machining pinion of hypoid gear,according to the cutting coordinate system of milling cutter and tooth surface equation,the mathematical model of machining pinion of hypoid gear is established,the theoretical tooth surface equation of pinion. The theoretical tooth surface is dispersed,the coordinates of the discrete points are solved,the tooth surface points are imported into UG and the modeling of tooth surface is carried out. According to the anti-conjugate principle,the tooth surface equation and tooth surface points of tool gear that fully conjugated with pinion are solved and three dimensional modeling is carried out. The motion simulation of three dimensional model is carried out,through the contact area to verify the correctness of modeling. According to the principle of equal volume,the rolling round billet is solved. Introduced the rolling models into DEFORM to carry out numerical simulation. The feasibility of the processing technology is verified by the simulation result,and theoretical guidance for the follow-up experiment is provided.